Life Under Exceptional Conditions - Isotopic Niches of Benthic Invertebrates in the Estuarine Maximum Turbidity Zone - Thomas Taupp; Claudia Hellmann; René Gergs; Carola Winkelmann; Markus A. Wetzel (Estuaries and Coasts, 2017)
The estuarine maximum turbidity zone (MTZ) can be assumed to be a stressful environment featuring special conditions of great biological importance with an excess of organic matter, high deposition rates, large variations in salinity, and dredging activities. Under such harsh conditions, populations may remain below the carrying capacity and competition is assumed to be of little importance, as predicted by the stress gradient hypothesis. Therefore, we hypothesized that invertebrates of similar feeding types may utilize the same resources. To test our hypothesis, we chose the three most abundant taxa classified in literature as deposit feeders (Bathyporeia pilosa, Boccardiella ligerica, Marenzelleria sp.) and two taxa classified as predominately predacious (Palaemon longirostris, Crangon crangon) and determined their isotopic niches based on a stable isotope analysis for the MTZ of the Elbe Estuary (Germany). We expected the isotopic niches of similar feeding types to show a clear overlap if our hypothesis was true. Our results showed that the isotopic niches of no two taxa overlapped within each feeding group, indicating different resource use and the absence of competition. The sediment analysis revealed that two of the deposit feeders inhabited significantly different mean grain sizes. The lack of overlap of isotopic niches within each feeding group may be due to differences in habitat and feeding behavior in the case of the deposit feeders and due to different migration behavior in the case of the predominately predacious species. However, competition may have occurred in the past, resulting in a divergence of feeding niches during evolution.

Leaving the beaten track - Approaches beyond the Venice System to classify estuarine waters according to salinity - Thomas Taupp; Markus A. Wetzel (Estuarine, Coastal and Shelf Science, 2014)

Relocation of dredged material in estuaries under the aspect of the Water Framework Directive - A comparison of benthic quality indicators at dumping areas in the Elbe estuary - Thomas Taupp; Markus A. Wetzel (Ecological Indicators, 2013)